2014
DOI: 10.31254/jsir.2014.3111
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological screening of Coccinia grandis Linn.

Abstract: Ethanol extract of Coccinia grandis Linn. (Family- Cucurbitaceae) were subjected to Phytochemical screening, which showed the presence of Alkaloids, Reducing sugar and Saponins. The pharmacological interest of these compounds, coupled with the use of this plant in traditional medicine encouraged to check Coccinea grandis (Linn.) for possible antimicrobial, antidirrhoeal and analgesic activities. The ethanolic extract at the dose of 500 mg/kg exhibited marked action against pain, (p<0.001), percentage of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The qualitative phytochemical screening test results were demonstrated in Table II Except for anthraquinones, the findings of the current qualitative analysis of phytochemicals indicated that all shade dried, oven-dried and freeze-dried leaf plant ethanolic extracts consisted of several bioactive compounds, including alkaloids, saponins, phenols, polyphenols, tannins, terpenoids, steroids, flavonoids, and phytosterols. Based on the results in Table II Previous studies reported that flavonoids and tannins were not present in sun-dried C. grandis leaf ethanolic extract [29]. In addition to that, [30] reported that the air-dried G. sylvestre leaf ethanolic extract was not contained terpenoids, steroids, coumarins and quinones.…”
Section: B Qualitative and Quantitative Analysis Of Phytochemicals In...mentioning
confidence: 88%
“…The qualitative phytochemical screening test results were demonstrated in Table II Except for anthraquinones, the findings of the current qualitative analysis of phytochemicals indicated that all shade dried, oven-dried and freeze-dried leaf plant ethanolic extracts consisted of several bioactive compounds, including alkaloids, saponins, phenols, polyphenols, tannins, terpenoids, steroids, flavonoids, and phytosterols. Based on the results in Table II Previous studies reported that flavonoids and tannins were not present in sun-dried C. grandis leaf ethanolic extract [29]. In addition to that, [30] reported that the air-dried G. sylvestre leaf ethanolic extract was not contained terpenoids, steroids, coumarins and quinones.…”
Section: B Qualitative and Quantitative Analysis Of Phytochemicals In...mentioning
confidence: 88%
“…Aqueous and ethanolic extracts of the plant have shown hypoglycemic principles. This plant has been used to treat diabetics, skin diseases, and jaundice [18,19]. Antioxidant, antimutagenic, antibacterial, antiulcer, hepatoprotective, expectorants, and analgesic properties have been documented, and anthelmintic, cytotoxic, anti-diabetic, mast cellstabilizing, anti-anaphylactic, and antihistaminic potential, antimitotic, and anti-inflammatory activities also reported [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…[10] Antibacterial, antifungal, antimicrobial, antiulcer, antioxidant, anti-inflammatory, antihyperglycemic, anti-cancer, anti-diabetic, anti-hepatotoxic, anti-inflammatory, anti-helminthics, anti-virus, anti-bacterial, anti-microbial [10] 3 Coccinia grandis (L.) Voigt Ivy Gourd, Kundru, Tondli Steroid, carbohydrates, tannins, flavonoids, saponins, alkaloids bamyrine, lupeol, cucubbitacin, cephalandrol, cephalandrine. [15] Antibacterial, Anthelmintic, Antioxidant, antiulcer, antimalarial, anti-inflammatory, antipyretic, analgesic, hypoglycaemic, antifungal, Anti-dyslipidemic, Antitussive, anticancer, antitussive, mutagenic activity. [14] 4…”
Section: Name Of Plantmentioning
confidence: 99%